Learning to Draw Through Digital Modelling - Temple, Stephen (Design and Technology Education: An International Journal, 2016)
The education of architectural designers begins by learning drawing and digital modelling following the notion that students learn these new modes as instruments of thinking in design process. Curricular arguments persist about which mode should follow the other. Difficulties occur when one mode replaces the other. Students uninitiated to design seem to prefer the more immediate volumetric visualization of digital modelling over plans, sections, and elevations, representational views resulting from the un-real ‘viewpoint’ of the section-cut, a means only drawn out of reality through a way-of-looking NOT natural-to-experience. Therefore, the primary difficulty in learning to think through drawings is their abstraction from, rather than connection to, realness – a needless initiating ordeal that confuses rather than clarifies. Digital modelling offers virtual three-dimensional images that seem to students, by contrast, not quite as abstracted from natural experience, albeit framed by non-physical, seductive, machine ‘otherness’. This paper proposes drawing pedagogy that learns from digital modelling by making connections rather than distinctions that more seamlessly connect abstract to actual. Projects will be demonstrated that manipulate three-dimensional forms to initiate drawing learning experiences. Drawing and its abstractions can thus more readily be drawn out of experience and made ultimately more concrete for design thinking.